The Role of the Teacher in Improving Student Discipline Through Catholic Religious Education Learning at Graphic Bina Media Vocational High School - Paulinus Tibo; Erikson Simbolon; Sinta Manuella Brother Tarigan (Indonesian Journal of Educational Science and Technology, 2023)
This study aims to determine the role of teachers in increasing student discipline through learning Catholic religious education at Graphic Bina Vocational High School Medan. This study uses a qualitative method. The data obtained from this study are in the form of primary data and secondary data. Data analysis used in this study is data reduction, data presentation and conclusion. Data collection techniques in this study were interviews, observation and documentation. There were 3 informants in this study consisting of 1 school principal, 4 teachers including PAK teachers and 13 students. The findings of this study are that PAK teachers have carried out their role in increasing student discipline at Graphic Bina Media Medan Vocational School so that student discipline has increased through learning Catholic Religious Education.